Specific jurisdiction in disputes of public utilities in the light of laws and jurisprudence - kilali, zahra (Milev Journal of Research and Studies, 2016)
This Although the pros that register on the Civil Procedure Code and administrative –principally singled specialized part of administrative disputes and procedures before the judiciary-, but he did not devoid of many of the gaps exposed by the applications later. And is the subject of the distribution of jurisdiction between the ordinary administrative and judicial authorities most important of these gaps and the most complex, distribution, although it put arbiter between specialists, but did not constitute a precision and clarity are spent on the intensification of conflicts between the judicial authorities, and to eliminate the presence of conflict is proof of this. In this presentation we refer to one administrative disputes that provoked considerable controversy in the courtyard of the judiciary topics, the subject of disputes, public facilities, by searching in the most important criteria adopted by the Algerian legislature to determine the jurisdiction of the qualitative in these disputes, especially as he did not make individually jurisdiction of the administrative by the judiciary never make it, but also of the jurisdiction of the ordinary courts in our study, relying on laws and jurisprudence.